Pathophysiology of carpal tunnel syndrome - Aboonq, Moutasem S. (Neurosciences (Riyadh), 2015)
Carpal tunnel syndrome (CTS) is the most common median nerve neuropathy, accounting for 90% of all neuropathies. Carpal tunnel syndrome presents in 3.8% of the general population, with a higher prevalence among women. There are several risk factors associated with CTS, including both medical and non medical factors. The pathophysiologic mechanisms involved in the median nerve compression and traction are thought to be complex, and as yet are not fully understood. The present review aimed to provide an overview of the pathophysiology of median nerve neuropathy in the carpal tunnel, and subsequent development of CTS.